Atomic routing in a deterministic queuing model - T. L. Werth; M. Holzhauser; Sven O. Krumke (Operations Research Perspectives, 2014)
The issue of selfish routing through a network has received a lot of attention in recent years. We study an atomic dynamic routing scenario, where players allocate resources with load dependent costs only for some limited time.
Keywords: 330; (I) Game theory; (B) Routing; Dynamic atomic unsplittable flows; Equilibria; Optimal solutions; Complexity